2021
DOI: 10.1146/annurev-psych-072720-094140
|View full text |Cite
|
Sign up to set email alerts
|

Active Forgetting: Adaptation of Memory by Prefrontal Control

Abstract: Over the past century, psychologists have discussed whether forgetting might arise from active mechanisms that promote memory loss to achieve various functions, such as minimizing errors, facilitating learning, or regulating one's emotional state. The past decade has witnessed a great expansion in knowledge about the brain mechanisms underlying active forgetting in its varying forms. A core discovery concerns the role of the prefrontal cortex in exerting top-down control over mnemonic activity in the hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
172
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(192 citation statements)
references
References 169 publications
19
172
1
Order By: Relevance
“…It has been revealed that arousal plays a role in voluntary forgetting of emotional materials (Zwissler et al., 2012), for example, highly arousal negative materials are exempt from voluntary forgetting (Hauswald et al., 2010). Therefore, we suggest including highly arousing social events (such as interpersonal conflict, divorce, and loss of relatives) in future work to extend the current findings and provide insights for the treatments of mental disorders characterized by deficient control of unwanted memory (Anderson & Hulbert, 2020; Nørby, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…It has been revealed that arousal plays a role in voluntary forgetting of emotional materials (Zwissler et al., 2012), for example, highly arousal negative materials are exempt from voluntary forgetting (Hauswald et al., 2010). Therefore, we suggest including highly arousing social events (such as interpersonal conflict, divorce, and loss of relatives) in future work to extend the current findings and provide insights for the treatments of mental disorders characterized by deficient control of unwanted memory (Anderson & Hulbert, 2020; Nørby, 2018).…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, a similar effect on brain activity was observed when some memories were effectively forgotten due to voluntary efforts to suppress them in the Think/NoThink paradigm 11 . Such suppression-induced forgetting of unwanted memories is positively associated with the downregulation of the hippocampal activity caused by the right dorsolateral prefrontal cortex (DLPFC), as demonstrated by several effective connectivity studies 17,18 .…”
Section: Discussionmentioning
confidence: 60%
“…A potentially similar phenomenon based on suppressing alternative memories is retrieval-induced forgetting (RIF), when selective retrieval causes forgetting of a memory competing for awareness 10 . Notably, this effect was observed for various stimuli ranging from visual objects and actions to autobiographical memories and word fragment completion 11 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…When people and rats retrieve a past event, other memories that compete with and hinder retrieval are more likely to be forgotten (Anderson et al, 1994). This 'retrieval-induced forgetting' occurs for a broad range of stimuli and contexts (Anderson and Hulbert, 2021;Anderson and Marsh, 2021). In humans, RIF arises because trying to retrieve a specific memory triggers inhibitory control mechanism mediated by the lateral prefrontal cortex that focus retrieval on goal-relevant traces by suppressing distracting memories (Anderson and Spellman, 1995;Anderson, 2003).…”
Section: Introductionmentioning
confidence: 99%